RELATIONSHIP OF COMMUNITY KNOWLEDGE AND ATTITUDE WITH DENTAL COLORING (STAIN) IN PEUNITI VILLAGE BANDA ACEH CITY - reca reca; Ainun Mardiah (Poltekkes Kemenkes Jambi, 2019)
Tooth staining (stain) is the color that sticks to the surface of the tooth usually occurs because of the attachment of the color of food, drinks or nicotine content. Community behavior is one of the factors that can affect dental and oral hygiene standards, one of which is staining. The purpose of this study was to determine the relationship between knowledge and attitudes of the community with staining in the Peuniti village of Banda Aceh city. This research is analytical with cross sectional approach. The population in this study is that the entire community in Peuniti village and the sample amounted to 30 people and were taken based on purposive sampling technique. Data obtained by interviews using questionnaires. The results showed that there was a relationship between knowledge and attitudes of the community with staining in the Peuniti village of Banda Aceh city (p <0.05). It can be concluded that there is a relationship between people's knowledge and attitudes with staining and it is recommended that all people reduce smoking, coffee and tea and reduce bad habits that can affect stain.